(The Potencies and Develpopmet Prospect of Palm Oil Industry Downstram in Indonesia) - Sudibyo, Agus (Warta Industri Hasil Pertanian, 2004)
The indonesian palm oil production in 2005 will reach about 11.3 milion tons and it is estimated that palm oil production still continue increasing for the next ten years .however ,eighty percent of palm oil exported from indonesia was crude palm oil (CPO) whereas a big of domestic consumption of CPO is consumed in edible oils in term of frying oil margarine and shortening on the contrary ,palm oil downstream industry and biodiesel industry is less develop is less than in malaysia; in point of fact the value added products that produce from palm oil downstream processing industry can reached 50 to 300 percent higher than in edible oil processing industry .the increasing demad palm oil ,the environmental friendly derived products of palm oil and the scarcity of petrochemical scour will open wide market of the palm oil the to develop palm oil based on the downstream processed products of palm oil than tends to increase in demand is very important this article reviews the existing of technology potency for the palm oil downstream processing industry development and its implementation possibility ,development prospect of the palm oil downstream processing industry ,and the line of the policy development.